Intra- and interobserver agreement on cervical volume and flow indices during pregnancy using transvaginal 3-dimensional ultrasonography and Doppler angiography - (:unkn) unknown (MEDICAL SCIENCE PUBLISHING INTERNATIONAL, INC, 2006)
Objectives-To assess intra- and interobserver agreement in cervical volume and flow indices measurements. Methods-We prospectively examined 126 patients by two seperate observers using transvaginal 3D gray-scale and power Doppler ultrasound. The two acquired volume datasets were analyzed using the VOCAL imaging program for assessing cervical volume, vascularization index (VI), flow index (FI), and vascularization flow index (VFI). Reproducibility of volume and vascularity measurement was assessed by calculating intraclass (intra-CC) and interclass (inter-CC) correlation coefficients (ICCs). Results-Both intraobserver and interobserver cervical volume measurements were in perfect agreement with intra-CC values of 0.95, 0.96 for both examiners and with an inter-CC value of 0.95. Intraobserver agreement for VI, FI and VFI measurements were as good as the interobserver agreement for VI, and VFI measurements were adequate but less for FI measurements (inter-CC 0.67). Overall, volumetric data were more reliably acquirable than power Doppler measurements. Conclusions-3D ultrasound gray-scale and power Doppler measurement of cervical volume and vascularization have acceptable intra- and interobserver variations and thus may be used in clinical research of cervical physiology and pathophysiology during pregnancy.
Keywords: three-dimensional ultrasound; VOCAL; cervical volume; reproducibility; power Doppler; OVARIAN VOLUME; GRAY-SCALE; REPRODUCIBILITY; ULTRASOUND; RELIABILITY; SONOGRAPHY; WOMEN